Avaliação da resposta de bovinos Nelore e cruzados, Senepol x Nelore e Angus X Nelore, infestados com carrapato Rhipicephalus (Boophilus) microplus - Ibelli, Adriana Mércia Guaratini (2012)
Infestations caused by ectoparasites are among the main problems that affect stock raising in tropical countries, and in Brazil, the Rhipicephalus (Boophilus) tick is responsible for substantial losses in the animal production. The aim of this study was to evaluate the response of three genetic groups of cattle artificially infested with Rhipicephalus (Boophilus) microplus. For this, skin samples from Nellore (NX) and crossbreeds, Senepol x Nellore (SN) and Angus x Nellore (TA) heifers were collected before and 24 hours after the last artificial infestation with Rhipicephalus (Boophilus) microplus larvae for gene expression analysis and histology. We collected hair and performed behavioral analysis in order to relate them to the cattle parasite load. There were significant differences (P <0.01) for the tick count within three studied groups. TA animals (0.92 ± 0.07) had higher mean and the NX group (0.28 ± 0.07), the lowest mean. In the differential leukocyte count, TA animals had higher numbers of monocytes that NX (P <0.05), not differing from SN. No significant differences were evaluated for other leukocytes. However, the NX genetic group had higher mean for mast cells than SN and TA (P <0.01). NX had more CD4 cells that TA that did not differ from SN. Negative correlation was observed between the number of ticks and CD4 T cells. In the hair and haircoat analysis, TA showed the higher values of haircoat mean (CP) and mass density (MD) of hair than SN and NX (p <0.05), which did not differ from each other. For the number of hairs per sample and number of hair/cm2, NX had larger mean (p <0.05) than SN and TA, which did not differ. Results of Pearson correlations indicated that CP and DM have a positive correlation (p <0.05) with tick count. Regarding grooming behavior it has been observed that the total of self-grooming, as well as, allogrooming events influenced the tick count evaluated, and that there is a negative correlation with the tick number, helping to reduce this parasite, especially in Nellore. On 1, 4, 6 and 7 days after infestation and at the times 7:00, 9:00 and 12:00 h animals performed more grooming events when compared to other periods. According to the large scale gene expression results, there was no difference within genetic groups. The comparison between the groups before and after 24 hours infestation showed that 1,502 genes were differentially expressed. Of these, 851 were activated and 651 had reduced expression after challenge. The microarray experiment was validated by quantitative real time PCR. 12 Among the genes and pathways activated in response to tick, the chemokine genes, MAPK signaling pathways and Jak-Stat, cytokine receptors, complement and focal adhesion molecules as well as calcium channel genes stood out. Such genes and pathways can be identified as candidates to play the role of host protection at this time of bovine parasitic cycle. In this way, it was observed that mechanisms as grooming and increase of mast cells should confer resistance to tick. Furthermore, we found metabolic pathways that were not previously described in the literature may be novel targets for the development of strategies prevent tick infestation, as vaccines and drugs.